Performance Analysis of Solar PV System with Tilt Angle Optimization to Enhance Energy Efficiency - Khairuddin, Muhammad Alif Aiman; Abd Rahman, Rahisham; Rizwan Ahmed; Bala Murugan Krishnan; Totok Dewantoro; Gezaq Abror (Evolution in Electrical and Electronic Engineering, 2026)
Solar energy is a key component of clean, green energy technology to meet the rising demand for electricity in today’s world. Solar system efficiency is dependent on many factors, including installation quality, measurement instruments, and cost analysis. Solar system installation plays a vital role in energy production. Poor installation leads to lower energy output, high cost and system failure. The accuracy of measurement instrumentation helps identify key parameters such as solar irradiance, voltage, and current. The main objective of this research work is to analyse the relationship between installation quality, measuring instruments, and their cost. Simulation tools are used to model the real-world case study scenario and analyse the effect of the tilt angle on solar system performance. The findings indicate that high installation quality can enhance measurement precision, leading to more reliable performance and better financial outcomes. Accurate instrumentation lowers maintenance costs and increases operational efficiency, thereby promoting the long-term sustainability of the solar system project.